2012
DOI: 10.1074/jbc.m111.322271
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U Type 1 Receptor Stimulation of A-type K+ Current Requires the βγ Subunits of Go Protein, Protein Kinase A, and Extracellular Signal-regulated Kinase 1/2 (ERK1/2) in Sensory Neurons

Abstract: Background: Regulation of I A has an important role in determining the electrical properties of dorsal root ganglion neurons. Results: Neuromedin U (NMU) increases I A via NMUR1 that couples to the ␤␥ subunits of G o protein, PKA, and ERK. Conclusion: NMUR1 stimulation of I A contributes to neuronal hypoexcitability. Significance: Selective regulation of I A by G protein-coupled receptors will contribute to neuronal excitability and subsequent transmission of the nociceptive electrical signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 57 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…In addition, we show in this study that NMUR2 was expressed in adult rat ventricular myocytes, whereas NMUR1 expression could not be detected. These receptor distribution patterns have started to allow the assignment of particular physiological roles of NMS and its receptors in mammalians [6,20,26]. By using genetic model, previous studies have shown that activation of NMUR1 inhibited L-type Ca 2+ channel currents in mouse hippocampal neurons [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we show in this study that NMUR2 was expressed in adult rat ventricular myocytes, whereas NMUR1 expression could not be detected. These receptor distribution patterns have started to allow the assignment of particular physiological roles of NMS and its receptors in mammalians [6,20,26]. By using genetic model, previous studies have shown that activation of NMUR1 inhibited L-type Ca 2+ channel currents in mouse hippocampal neurons [26].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed following the procedure described by previous reports [18][19][20]. For antibody detection, after incubated with 5% non-fat milk in TBST for 1 h at room temperature, membranes were then incubated with diluted primary antibody goat anti-rat NMUR1 (Santa Cruz, 1:500) or NMUR2 (Santa Cruz, 1:500) and incubated at 4 °C overnight.…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blotting-Western blot analysis was performed as described previously (30,31). Briefly, total cellular protein was extracted from rat ventricular myocytes using homogenization buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [17,24,25]. In brief, cells were homogenized by sonication at 4 °C in homogenization buffer containing protease inhibitors.…”
Section: Western Blottingmentioning
confidence: 99%